Reading Between the Lines : The Neolithic Cursus Monuments of Scotland - Brophy, Kenneth (Taylor and Francis, 2015)
Reading Between the Lines- Front Cover -- Reading Between the Lines -- Title Page -- Copyright Page -- Dedication -- Contents -- Figures -- Tables -- Acknowledgements -- Dating conventions -- Part I: The sites and their context -- Chapter 1: 'The weirdest type of field monument in the country' -- The dowsing man -- The cursus problem -- Cropmarks and cursus monuments -- Conclusion -- Chapter 2: How do you solve a problem like a cursus? -- Origins -- From the air -- 1947 -- The Dorset cursus effect -- The cursus problem -- The fourth-millennium DC (Dorset cursus) -- Themes of cursus studies -- Conclusion -- Chapter 3: Bust and boom -- A fresh perspective -- The Cambridge factor -- Boom: RCAHMS aerial survey -- '. . . a little judicious excavation in the right spot' -- 'The rear-end of an undomesticated duck': chasing cursus monuments in the 1990s -- Rethinking Scotland's cursus monuments -- Chapter 4: Ditches and banks, pits and postholes -- A cautionary tale -- Defining Scotland's cursus monuments -- The location and distribution of Scotland's cursus monuments -- The timber cursus monuments -- Hooray for Holywood -- Earthwork cursus monuments -- The Cleaven Dyke -- Dating Scotland's cursus monuments -- Little and large -- Chapter 5: Scotland in the early Neolithic: The world of the cursus builders -- The early Neolithic context -- The first farmers and the first 'farms' -- Monuments: ceremony, ritual and death -- Conclusion -- Part II: The evidence reviewed -- Chapter 6: Grand designs -- Introduction -- Building sites -- Targets and goals: cursus terminals -- Project management: cursus wobbliness -- Extensions or partitions? Internal divisions -- Running repairs -- Conclusion -- Chapter 7: Special places -- Going through a phase -- B.C. (Before Cursus) -- Cursus connections -- Settlement evidence -- Cursus pairs.